The effect of ostrich oil and breast milk on healing of breast fissures in lactating primiparous women - Masumeh Koushki; Faraz Mojab; Rasool mohammadi; Seideh Hanieh Alamolhoda (Mashhad University of Medical Sciences, 2024)
Introduction: Breast fissure is a disorder during breastfeeding that causes the lack of successful breastfeeding. Considering its high prevalence and due to the anti-inflammatory properties of ostrich oil, this study was conducted with aim to compare the effect of ostrich oil and breast milk on the improvement of breast fissures in lactating primiparous women. Methods: This clinical trial study was conducted on 106 lactating primiparous women in 2022-2023. Mothers were divided into two groups of ostrich oil and breast milk (n=53 in each group). After teaching the correct method of breastfeeding, they continued the treatment 3 times a day for one week. In the intervention group, lactating women covered the nipple and the surrounding area with ostrich oil, and in the control group with their breast milk, for one consecutive week. The intensity of pain and nipple fissure score were recorded by the researcher based on the quality of visual analogue and the result of Store. Data analysis was done using SPSS statistical software (version 25) and independent t-test, paired t-test, chi-square, analysis of variance with repeated data and Fisher's exact tests. P<0.05 was considered statistically significant. Results: The mean nipple pain before the intervention was not significant in the two groups (p=0.659), but there was a statistically significant difference between the two groups on the 7th and 10th days after delivery (p<0.001). There was a significant difference in the severity of nipple damage before and after the intervention in the two groups (p<0.001); So that the severity of damage in the ostrich oil group was higher before the intervention and less during the 7 days of treatment. Conclusion: Ostrich oil improves breast fissures and reduces nipple pain.